Project-Based Assessment in English for Specific Purposes - Siti Asmiyah (STKIP AL HIKMAH SURABAYA, 2020)
Project Based Learning (PBL) in English for Specific Purpose (ESP) has been believed to enable student to have hand on and contextual experiences related to their English Language Learning. In addition to the teaching and learning process, project can also be used as an assessment instrument through PBL. Despite the possible project-based assessment, the existing studies have mainly focused on the PBL as a teaching and learning approach with less attention on assessment. This paper describes the use of project based assessment in two ESP courses in an Islamic college in East Java. The stages of the assessment and students’ responses on the benefit and challenges are presented. Implication for PBL in English language teaching and learning and other possible implementation of project-based assessment are also presented in the paper.